2013
DOI: 10.1080/08897077.2012.691453
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in Selfishness Explain 12-Step Benefit? A Prospective Lagged Analysis

Abstract: Objective 12-step attendance is associated with increased abstinence. A strong claim made in 12-step literature is that alcoholics are pathologically selfish and that working the 12 steps reduces this selfishness which, in turn, leads to sustained alcohol abstinence. This study tested this assumption by investigating the linkages between 12-step attendance, pathological narcissism, and drinking. Method 130 early AA affiliates with limited AA and treatment histories were recruited from treatment and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…One of the paradoxes in the Twelve-Step approach is that members simultaneously learn that service to others is crucial to recovery, but that "it is a selfish program," (a popular epigram). A recent study of new AA members found the Twelve Steps are associated with recovery, but are not associated with reductions in pathological narcissism (Tonigan, Rynes, Toscova, & Hagler, 2012). A similar study of Al-Anon members might reveal whether narcissism is associated with recovery for COs and whether codependent members are susceptible to developing extreme narcissism.…”
Section: Perpetuating Victimizationmentioning
confidence: 96%
“…One of the paradoxes in the Twelve-Step approach is that members simultaneously learn that service to others is crucial to recovery, but that "it is a selfish program," (a popular epigram). A recent study of new AA members found the Twelve Steps are associated with recovery, but are not associated with reductions in pathological narcissism (Tonigan, Rynes, Toscova, & Hagler, 2012). A similar study of Al-Anon members might reveal whether narcissism is associated with recovery for COs and whether codependent members are susceptible to developing extreme narcissism.…”
Section: Perpetuating Victimizationmentioning
confidence: 96%
“…Also, AA participation and, specifically, increased spirituality have been shown to explain lower depression among individuals with alcohol use disorder (AUD) [37]. Conversely, methodologically rigorous studies since the initial review testing AA's other major purported AA mechanisms, such as reduced selfishness/selfcenteredness [38] and reduced anger/resentment [39], have not been supported. While studies have also shown that the benefit conferred by AA may be explained partially by reducing depressive symptoms [37,40], craving [41] and impulsivity [42], with a few exceptions [43][44][45] these studies of AAs mechanisms typically only tested models using a single mediator (e.g.…”
Section: Mechanisms Research On Aamentioning
confidence: 99%
“…First, the AA literature emphatically states that the reduction of negative affect is instrumental for achieving abstinence (AA, 2001). Here, investigators have prospectively examined how frequency of AA meeting attendance is associated with negative affect, including reductions in depression (Kelly et al, 2010a; Wilcox et al, in press ), anger (Kelly et al, 2010b), and selfish narcissism (Tonigan et al, 2013). Findings from these studies have been relatively consistent: (1) AA members report, on average, clinically elevated levels of depression, anger, and selfish narcissism at baseline, and (2) modest changes over time, but (3) measures of negative affect have limited prognostic value in predicting subsequent alcohol use.…”
Section: Improving 12-step Treatment By Understanding Aa Bettermentioning
confidence: 99%